Cathelicidin-mediated lipopolysaccharide signaling via intracellular TLR4 in colonic epithelial cells evokes CXCL8 production. Issue 1 (9th November 2020) - Holani, Ravi; Babbar, Anshu; Blyth, Graham A. D.; Lopes, Fernando; Jijon, Humberto; McKay, Derek M.; Hollenberg, Morley D.; Cobo, Eduardo R.
ABSTRACT: We hypothesized that the antimicrobial peptide cathelicidin has a physiological role in regulating gut inflammatory homeostasis. We determined that cathelicidin synergizes with LPS to facilitate its internalization and signaling via endosomic TLR4 in colonic epithelium, evoking synthesis of the human neutrophil chemoattractant, CXCL8 (or murine homolog, CXCL1). Interaction of cathelicidin with LPS in the control of CXCL8/CXCL1 synthesis was assessed in human colon epithelial cells, murine colonoids and cathelicidin-null mice ( Camp −/- ). Mechanistically, human cathelicidin (LL-37), as an extracellular complex with LPS, interacted with lipid raft-associated GM1 gangliosides to internalize and activate intracellular TLR4. Two signaling pathways converged on CXCL8/CXCL1 production: (1) a p38MAPK-dependent pathway regulated by Src-EGFR kinases; and, (2) a p38MAPK-independent, NF-κB-dependent pathway, regulated by MEK1/2-MAPK. Increased cathelicidin-dependent CXCL8 secretion in the colonic mucosa activated human blood-derived neutrophils. These cathelicidin effects occurred in vitro at concentrations well below those needed for microbicidal function. The important immunomodulatory role of cathelicidins was evident in cathelicidin-null/ Camp −/- mice, which had diminished colonic CXCL1 secretion, decreased neutrophil recruitment-activation and reduced bacterial clearance when challenged with the colitis-inducing murine pathogen, Citrobacter rodentium . We conclude that in addition to its known microbicidal action, cathelicidin has a unique pathogen-sensing role, facilitating LPS-mediated intestinal responses, including the production of CXCL8/CXCL1 that would contribute to an integrated tissue response to recruit neutrophils during colitis.